2013
DOI: 10.1186/1479-5868-10-10
|View full text |Cite
|
Sign up to set email alerts
|

Daily physical activity predicts degree of insulin resistance: a cross-sectional observational study using the 2003–2004 National Health and Nutrition Examination Survey

Abstract: BackgroundThis study examined the independent association of objectively measured physical activity on insulin resistance while controlling for confounding variables including: cardiorespiratory fitness, adiposity, sex, age, and smoking status.MethodsData were obtained from National Health and Nutrition Examination Survey 2003–2004, a cross-sectional observational study conducted by the National Center for Health Statistics of the Centers for Disease Control that uses a stratified, multistage probability desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
42
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 28 publications
3
42
0
Order By: Relevance
“…This study is in agreement with this fact as results obtained revealed a reduction post-exercise in HOMA-IR levels in both sexes, though these changes were insignificant, apparently due to the short time frame of the exercise program. This is in agreement with the earlier finding by Rachael [21] that regular exercise lowers insulin resistance.…”
Section: Discussionsupporting
confidence: 94%
“…This study is in agreement with this fact as results obtained revealed a reduction post-exercise in HOMA-IR levels in both sexes, though these changes were insignificant, apparently due to the short time frame of the exercise program. This is in agreement with the earlier finding by Rachael [21] that regular exercise lowers insulin resistance.…”
Section: Discussionsupporting
confidence: 94%
“…A review study by Wanner et al (31) found out that active transportation was associated with increased PA (in cross-sectional studies reviewed). Similarly, meta-analyses (3, 15) demonstrated the effectiveness of community-based interventions on increasing PA in adults. The present study adds value to these lines of work by showing how adults’ MPVA in these two domains varies by socio-demographic factors.…”
Section: Discussionmentioning
confidence: 99%
“…16 Yet fewer than half of all adults meet the 2008 Physical Activity Guidelines, 7 which include at least 150 minutes per week of aerobic (e.g. brisk walking) and muscle-strengthening activities that involve all major muscle groups, on two or more days per week.…”
Section: Introductionmentioning
confidence: 99%